Multi-Frame Motion-Compensated Prediction for Video Transmission - Wiegand, Thomas; Girod, Bernd (Springer US, 2001)
Multi-Frame Motion-Compensated Prediction for Video Transmission presents a comprehensive description of a new technique in video coding and transmission. The work presented in the book has had a very strong impact on video coding standards and will be of interest to practicing engineers and researchers as well as academics. The multi-frame technique and the Lagrangian coder control have been adopted by the ITU-T as an integral part of the well known H.263 standard and are were adopted in the ongoing H.26L project of the ITU-T Video Coding Experts Group. This work will interest researchers and students in the field of video coding and transmission. Moreover, engineers in the field will also be interested since an integral part of the well known H.263 standard is based on the presented material
Keywords: Computer Science; Image Processing and Computer Vision; Multimedia Information Systems; Electrical Engineering; Computer Graphics; Computer science; Multimedia information systems; Computer graphics; Image processing; Electrical engineering; Datenkompression; Prädiktionsanalyse; Codierung; Videoübertragung; Hochschulschrift